Effect of increasing the network capacity using device-to-device technology for next generation networks - Aws Zuheer Yonis (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Device-to-device (D2D) communication is one of the key technologies in the fifth generation of wireless communication systems, which is defined as direct communication between two mobile users without traversing the base station D2D communication plays an increasingly important role and which improves communication capability and reduces communication delay and power consumption. D2D communication that enables direct communication between nearby mobiles is an exciting and innovative feature of next-generation cellular networks. In order to meet the rising subscriber demands and provide them satisfactory services, D2D communication is being looked upon as an emerging technology of the next generation networks.